Diversity across EU Banking Sectors: Poorly Researched and Underappreciated - Hans-Helmut Kotz; Dorothea Schäfer (Vierteljahrshefte zur Wirtschaftsforschung, 2018)
Interest in the role of diversity in banking sectors has increased substantially since the financial crisis (and the subsequent sovereign debt crises) have hit European countries differentially. The purpose of this note is to hint at crucial research gaps in terms of appreciating consequences of this variety. In preparation for this, we take stock of the across country diversity of banking sectors in the European Union before and after the financial crisis. Key issues in a future research agenda for evaluating diversity in the banking sector (and the financial sector more generally) have to do with: (a) defining the concept's empirical meaning and hence its measurable properties, (b) the relationship between diversity and the level of competition (market power) in the banking sector, (c) the link between diversity and banking sector stability, (d) the pertinence of banking sector diversity for mitigating access to finance problems, in particular for SMEs and (e) the interlinkages between diversity in the banking (financial) sector and non-financial, “real” economy diversity (“goodness of fit”- issue, institutional embededdness). Filling the indicated research gaps would be an important contribution to both the debate on deeper integration of Europe's financial markets (Banking Union, Capital Markets Union) as well as the debate on a sustainable financial architecture, being at the same time conducive to innovation and growth whilst protecting society effectively from large-scale financial crises.
Keywords: G01; G20; G21; G28; 330; Diversity; banking sector structure; sector stability; SME; financial constraints